SYNTHESIS AND CHARACTERIZATION OF BOVINE SERUM ALBUMIN NANOPARTICLES AS A DRUG DELIVERY VEHICLE - S S ROHIWAL,; S H PAWAR, (International Journal of Pharma and Bio Sciences, 2014)
Nanoparticles prepared from Bovine serum albumin (BSA) are versatile carrier systems for drug delivery and can be prepared by an established desolvation process, under the aspect of the controllable particle size range between 100 to 300 nm with narrow size distribution. Various components were evaluated influencing the size of BSA nanoparticles (BSA NPs) viz pH, salt content and the conditions for purification. Washing the particles by subsequent cycles of differential centrifugation significantly led to decrease in the poly disparity index (PDI). FTIR was used to determine the purity of the prepared BSA NPs. Atomic Force Microscopy (AFM) and Field emission scanning electron microscopy (FE-SEM) displays the size and spherical shape of nanoparticles. Zeta potential with varying pH unveils the surface charges of BSA NPs. The size controlled BSA nanoparticles can be used as the standard material for drug loading capacity for bioactive molecules.